Advances in sprint acceleration profiling for field-based team-sport athletes: Utility, reliability, validity and limitations - Simperingham, K. D.; Cronin, J. B.; Ross, A. (Sports Medicine, 2016)
Advanced testing technologies enable insight into the kinematic and kinetic determinants of sprint acceleration performance, which is particularly important for field-based team-sport athletes. Establishing the reliability and validity of the data, particularly from the acceleration phase, is important for determining the utility of the respective technologies. Objective: The aim of this systematic review was to explain the utility, reliability, validity and limitations of (1) radar and laser technology, and (2) non-motorised treadmill (NMT) and torque treadmill (TT) technology for providing kinematic and kinetic measures of sprint acceleration performance. Data Sources: A comprehensive search of the CINAHL Plus, MEDLINE (EBSCO), PubMed, SPORTDiscus, and Web of Science databases was conducted using search terms that included radar, laser, non-motorised treadmill, torque treadmill, sprint, acceleration, kinetic, kinematic, force, and power. Methods: Studies examining the kinematics or kinetics of short (=10 s), maximal-effort sprint acceleration in adults or children, which included an assessment of reliability or validity of the advanced technologies of interest, were included in this systematic review. Absolute reliability, relative reliability and validity data were extracted from the selected articles and tabulated. The level of acceptance of reliability was a coefficient of variation (CV) =10 % and an intraclass correlation coefficient (ICC) or correlation coefficient (r) =0.70. Results: A total of 34 studies met the inclusion criteria and were included in the qualitative analysis. Generally acceptable validity (r = 0.87-0.99; absolute bias 3-7 %), intraday reliability (CV =9.5 %; ICC/r =0.84) and interday reliability (ICC =0.72) were reported for data from radar and laser. However, low intraday reliability was reported for the theoretical maximum horizontal force (ICC 0.64) within adolescent athletes, and low validity was reported for velocity during the initial 5 m of a sprint acceleration (bias up to 0.41 m/s) measured with a laser device. Acceptable reliability of results from NMT and TT was only ensured when testing protocols involved sufficient familiarisation, a high sampling rate (=200 Hz), a `blocked` start position, and the analysis of discrete steps rather than arbitrary time periods. Sprinting times and speeds were 20-28 % slower on a TT, 28-67 % slower on an NMT, and only 9-64 % of the variance in overground measurements of speed and time (=30 m) was explained by results from an NMT. There have been no reports to date of criterion validity of kinetic measures of sprint acceleration performance on NMT andTT, and only limited results regarding acceptable concurrent validity of radar-derived kinetic data. Conclusions: Radar, laser, NMT and TT technologies can be used to reliably measure sprint acceleration performance and to provide insight into the determinants of sprinting speed. However, further research is required to establish the validity of the kinetic measurements made with NMT and TT. Radar and laser technology may not be suitable for measuring the first few steps of a sprint acceleration.